The currency of ideas : monetary politics in the European Union - McNamara, Kathleen R., 1962- (Cornell studies in political economy., 1998)
Why have the states of Europe agreed to create an Economic and Monetary Union (EMU) and a single European currency? What will decide the fate of this bold project? This book explains why monetary integration has deepened in Europe from the Bretton Woods era to the present day. McNamara argues that the development of a neoliberal economic policy consensus among European leaders in the years after the first oil crisis was crucial to stability in the European Monetary System and progress towards EMU. She identifies two factors, rising capital mobility and changing ideas about the government's proper role in monetary policymaking, as critical to the neoliberal consensus but warns that unresolved social tensions in this consensus may provoke a political backlash against EMU and its neoliberal reforms. McNamara's findings are relevant not only to European monetary integration, but to more general questions about the effects of international capital flows on states. Although this book delineates a range of constraints created by economic interdependence, McNamara rejects the notion that international market forces simply dictate government policy choice. She demonstrates that the process of neoliberal policy change is a historically dependent one, shaped by policymakers' shared beliefs and interpretations of their experiences in the global economy.